2016
DOI: 10.1021/acsami.6b08369
|View full text |Cite
|
Sign up to set email alerts
|

Application of Freeze-Dried Powders of Genetically Engineered Microbial Strains as Adsorbents for Rare Earth Metal Ions

Abstract: The adsorption behaviors of the rare earth metal ions onto freeze-dried powders of genetically engineered microbial strains were compared. Cell powders obtained from four kinds of strains, Bacillus subtilis 168 wild type (WT), lipoteichoic acid-defective (ΔLTA), wall teichoic acid-defective (ΔWTA), and cell wall hydrolases-defective (EFKYOJLp) strains, were used as an adsorbent of the rare earth metal ions at pH 3. The adsorption ability of the rare earth metal ions was in the order of EFKYOJLp > WT > ΔLTA > Δ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 36 publications
(55 reference statements)
1
18
0
Order By: Relevance
“…This essentially suggests that Nd­(III) adsorption is most effective in the lower dose. The adsorbed amount and distribution coefficient of Nd in MC-T100 are higher than those of other DNA-based materials, such as salmon milt powder or DNA-filter hybrid and other sorbents, including freeze-dried powder of genetically engineered microbial strains, EDTA- and DTPA-functionalized chitosan, and ion-imprinted mesoporous silica …”
Section: Results and Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This essentially suggests that Nd­(III) adsorption is most effective in the lower dose. The adsorbed amount and distribution coefficient of Nd in MC-T100 are higher than those of other DNA-based materials, such as salmon milt powder or DNA-filter hybrid and other sorbents, including freeze-dried powder of genetically engineered microbial strains, EDTA- and DTPA-functionalized chitosan, and ion-imprinted mesoporous silica …”
Section: Results and Discussionmentioning
confidence: 90%
“…Our previous research demonstrated a higher uptake of Nd and Dy compared to Fe­(III) in phosphorous-functionalized microporous carbon . The cell walls of different types of natural or genetically modified bacteria were employed for the capture of various REEs, and it was hypothesized that the phosphate functionality on the cell wall of bacteria strains is responsible for the affinity-based capture of these rare earth elements. , Recently, commercially available DNA-based materials have been employed to selectively capture REEs through their phosphorous and oxygen functionalities. Freeze-dried and powdered salmon milt as a source of DNA was employed to adsorb 15 REEs in a column process .…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the selectivity for Sc over Y and Nd was also observed for cell-free silica (Figure S3), albeit with much lower total adsorption compared to that of MESG (Figure S4). The selectivity of the MESG biosorbent for Sc is likely attributed to the ability of cell surface hard ligands (i.e., phosphate groups) and silanol groups on silica to form strong complexes with Sc­(III) ions, which has a smaller ionic radius and stronger Lewis acid characteristics compared to that of the lanthanides. , …”
Section: Resultsmentioning
confidence: 99%
“…Solid–liquid extraction (SLE) has emerged as an attractive alternative for Sc extraction due to the elimination of toxic, inflammable, and expensive organic solvents (diluent + extractant) and the facile reuse of adsorbent materials . A number of adsorbent materials have been developed for Sc recovery, including polyelectrolytes, carbon-based materials, polymer resins, and silica. These adsorbents exhibit high Sc adsorption capacity owing to their high surface area and abundant negatively charged functional groups, , but their utility to extract Sc in the presence of competing lanthanides remains largely unknown, a barrier for their application to low-grade Sc feedstocks. ,,,,, Microbe-mediated surface adsorption (biosorption) via metal complex formation with the surface functional group offers a potentially cost-effective and environmentally sustainable approach for SLE of REE from dilute feedstock sources. Previous work has shown that Sc was preferentially adsorbed to Bacillus subtilis and Escherichia coli when Sc was present at the same concentrations as the lanthanides. , Several yeast species were found to preferentially adsorb Sc over Y, Fe, and Al in both synthetic solutions and red mud leachates . While these initial studies are promising, it remains an open question, however, whether biosorption can be effectively applied for selective and scalable Sc recovery from relevant industrial feedstocks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation